Atypical B12 Deficiency with Nonresolving Paraesthesia - S. Haider; N. Ahmad; E. J. Anaissie; N. Abdel Karim (Case Reports in Oncological Medicine)
Vitamin B12 deficiency can present with various hematological, gastrointestinal and neurological manifestations. We report a case of elderly female who presented with neuropathy and vitamin B12 deficiency where the final work-up revealed polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS). This case suggests that, although POEMS syndrome is a rare entity, it can present with vitamin-B12 deficiency and thus specific work up for early diagnosis of POEMS should be considered in patients with B12 deficiency unresponsive to therapy.